Flexible Zirconium Metal‐Organic Frameworks as Bioinspired Switchable Catalysts. Issue 36 (27th June 2016) - Yuan, Shuai; Zou, Lanfang; Li, Haixia; Chen, Ying‐Pin; Qin, Junsheng; Zhang, Qiang; Lu, Weigang; Hall, Michael B.; Zhou, Hong‐Cai
Abstract: Flexible metal–organic frameworks (MOFs) are highly desirable in host–guest chemistry owing to their almost unlimited structural/functional diversities and stimuli‐responsive pore architectures. Herein, we designed a flexible Zr‐MOF system, namely PCN‐700 series, for the realization of switchable catalysis in cycloaddition reactions of CO2 with epoxides. Their breathing behaviors were studied by successive single‐crystal X‐ray diffraction analyses. The breathing amplitudes of the PCN‐700 series were modulated through pre‐functionalization of organic linkers and post‐synthetic linker installation. Experiments and molecular simulations confirm that the catalytic activities of the PCN‐700 series can be switched on and off upon reversible structural transformation, which is reminiscent of sophisticated biological systems such as allosteric enzymes. Abstract : An open and shut case : The inherent cavities and dynamic behavior of flexible MOFs, bear a close resemblance to regulatory enzymes. Switchable activation and deactivation of their catalytic properties occurs on pore opening and closing by solvation/solvent removal.